Stanovení ceny inženýrských činností ve výstavbě - Miháliková, Andrea (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Práce je zaměřena na stanovení cen inženýrských činností. V jednotlivých kapitolách jsem rozebrala rozdělení inženýrských činností. Definovala jsem jednotlivé činnosti. Vysvětlila jsem, co je to projektové řízení staveb, a rozebrala jsem jednotlivé formy projektů. Definovala jsem účastníky výstavbového procesu a vztahy mezi nimi. Dále jsem se zaměřila na správný výběr dodavatele. Nakonec jsem vysvětlila pojem cena, rozdělila ho na různé druhy, a porovnala metodiky tvorby cen. Výstupem práce je stanovení ceny inženýrských činností na základě metody doporučených minimálních a maximálních cen.

The work is focused on setting the prices of engineering activities. In the individual chapters, I discussed the division of engineering activities. I defined individual activities. I explained what project management of buildings is, and I analysed the various forms of projects. I defined the participants in the construction process and the relationships between them. I also focused of choosing the right supplier. Finally, I explained the concept of price, divided in into different types, and compared pricing methodologies. The output of the work is the determination of the price of engineering activities based on the method of recommended minimum and maximum prices.
Pricing of engineering activities in construction
Keywords: inženýrské činnosti; účastníci výstavbového procesu; cena; druhy cen; tvorba cen; engineering activities; participants in the construction process; price; types of process; pricing